Analysis of PAU Task Devices in Immigration Services at the Immigration Checkpoint (TPI) of I Gusti Ngurah Rai International Airport - Dharma Sanjaya; Ida Ayu Putu Sri Widnyani; Gede Wirata (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
The Passenger Analysis Unit (PAU) at I Gusti Ngurah Rai International Airport, Bali, plays a strategic role in analyzing international passenger data to support effective immigration control at the main gateway for foreign nationals and Indonesian citizens to enter Indonesia. The PAU is tasked with proactively profiling and risk assessments before passengers arrive through the Advance Passenger Information System (APIS), enabling early detection of potential violations or security risks such as criminal records or overstays. In addition to its immigration intelligence function, the PAU also ensures smooth public services by optimizing fast, accurate, and humane immigration administration processes, and integrating the use of technology for operational efficiency. Despite facing technical obstacles, inter-agency coordination, and public awareness that still needs to be improved, the PAU's existence is key to maintaining national security while improving the quality of public services at Ngurah Rai Airport, as one of the busiest and best airports in Asia. This research uses a qualitative method with a case study approach, because the main focus of the research is directed at the Passenger Analysis Unit (PAU) as a work unit operating at the Immigration Checkpoint (TPI) of I Gusti Ngurah Rai International Airport. This case study was chosen because it allows researchers to gain a deeper understanding of the immigration public service phenomenon implemented by the PAU in a concrete and specific context. Keywords: PAU, Immigration, Supervision